Constitutionalizing Sharia: Identity and Independence of Islamic Politics among Students - Khamami Zada; Mundzeir Suparta; Bambang Ruswadi; Harapandi Dahri; Mualimin Mochammad Sahid (Fakultas Syari'ah IAIN Batusangkar, 2024)
Indexed by Scopus